Prevalence of Malocclusion Among Adolescents In Central Anatolia - Gelgör, İbrahim Erhan; Karaman, İhya Ali; Ercan, Ertuğrul (European Journal of Dentistry, 2007)
Objectives: The objective of this study was to describe the prevalence of malocclusion in a population of Central Anatolian adolescents in relation to gender.Methods: The sample comprised 2329 teenagers (1125 boys and 1204 girls), aged between 12 and 17 years (mean age: 14.6 yrs). Occlusal anteroposterior relationships were assessed using the Angle classification. Other variables examined were overjet, overbite, crowding, midline diastema, posterior crossbite, and scissors bite.Results:The results showed that about 10.1% of the subjects had normal occlusions, 34.9% of the subjects had Class I malocclusions, 40.0% had Class II Division 1 malocclusions, 4.7% had Class II Division 2 malocclusions and 10.3% had Class III malocclusions. Over 53.5% had normal overbites, and 18.3%, 14.4%, 5.6%, and 8.2% had increased, reduced, edge-to-edge or anterior open bite values, respectively. Overjet relationship was normal in 58.9%, increased in 25.1%, reversed in 10.4%, and edge-to-edge in 5.6%. A posterior crossbite registered in 9.5% and scissors bite in 0.3%. Anterior crowding was present in 65.2% of the sample and midline diastema in 7.0%. No clear gender differences were noted, except for normal overbite (most frequent in girls, P>.001) and increased overbite (most frequent in boys, P>.05)Conclusions: Class II Division 1 malocclusion is the most prevalent occlusal pattern among the Central Anatolian adolescents and the high values (25.1% and 18.3%) of increased overjet and overbite were a reflection of the high prevalence of Class II malocclusion. (Eur J Dent 2007;1:125-131)
Keywords: Malocclusion; Class I malocclusions; Class II Division 1; Class III malocclusions